Benchmarking Gaussian Basis Sets in Quantum-Chemical Calculations of Photoabsorption Spectra of Light Atomic Clusters - Mahamiya, Vikram; Bhattacharyya, Pritam; Shukla, Alok (arXiv.org, 2023)
The choice of Gaussian basis functions for computing the ground-state properties of molecules, and clusters, employing wave-function-based electron-correlated approaches, is a well-studied subject. However, the same cannot be said when it comes to the excited-state properties of such systems, in general, and optical properties, in particular. The aim of the present study is to understand how the choice of basis functions affects the calculations of linear optical absorption in clusters, qualitatively, and quantitatively. For this purpose, we have calculated linear optical absorption spectra of several small charged and neutral clusters, namely, Li\(_{2}\), Li\(_{3}\), Li\(_{4}\), B\(_{2}^{+}\), B\(_{3}^{+}\), Be\(_{2}^{+}\), and Be\(_{3}^{+}\), using a variety of Gaussian basis sets. The calculations were performed within the frozen-core approximation, and a rigorous account of electron correlation effects in the valence sector was taken by employing various levels of configuration interaction (CI) approach both for the ground and excited states. Our results on the peak locations in the absorption spectra of Li\(_{3}\) and Li\(_{4}\) are in very good agreement with the experiments. Our general recommendation is that for excited-state calculations, it is very important to utilize those basis sets which contain augmented functions. Relatively smaller aug-cc-pVDZ basis sets also yield high-quality results for photoabsorption spectra, and are recommended for such calculations if the computational resources are limited.